Is the education on digital libraries adequate - Liu, Yan Quan (New Library World, 2004)
This study investigates the state of education for digital libraries. For this study, a Web survey was conducted of syllabi of courses on the subject of digital libraries (DL). Similarities and differences on such subjects as teaching emphases, course outlines, textbooks and assignments were compared. The majority of classes now contain a “hands-on” element, a practical component of the course that requires that the students interact with digital libraries. Not all of the course contents are up-to-date in the field of library and information technology. While the quality of DL education seems to have advanced at those schools and institutions that offer classes with “hands-on” requirements, the educational approach at many of the “hands-off” universities seems somewhat technophobic and overly dependent on outdated pedagogical methods. Those students who have received practical experience with digital libraries, like those provided in the “hands-on” courses, appear to be best served for future practice in the field of librarianship. © 2004, Emerald Group Publishing Limited
Keywords: Digital libraries; Europe; Libararies; Library facilities; North America; Surveys; dept.ils

Best practices, standards and techniques for digitizing library materials: a snapshot of library digitization practices in the USA - Liu, Yan Quan (Online Information Review, 2004)
This study investigates current practice in digitizing library materials in the USA. Building a good digital collection has been a common task, pervasive in all types of libraries. Digitization becomes more and more crucial, affecting libraries while they work towards becoming digital. Researchers and practitioners would like to know what practices have been developed to deal with the challenges that pose the most significant problems or concerns for libraries in digitization. Through probing some widespread issues on what materials to digitize, and the associated standards and technologies in digitization in US libraries, this survey of current literature reveals a number of prominent library digitization practices, methods and challenges, and highlights the best practices, trends and interests in library digitization pertaining to both policy and technology marketplace issues.
Keywords: Analog to digital conversion; Data processing; Digital libraries; Document image processing; Electronic media; Information and Library Science; Multimedia systems; Project management; Public policy; Societies and institutions; Standards; Technical problems; United States of America; dept.ils